The subspecies concept in Geocorinae: an integrated taxonomic case study on Geocoris (Piocoris) erythrocephalus (Lepeletier & Serville, 1825) (Hemiptera: Heteroptera: Geocoridae) - Kóbor, P.; Tóbiás, I.; Roca-Cusachs, M.; Kondorosy, E. (Zootaxa, 2018)
The validity and necessity of subspecies as a taxonomic category and the implications of the subspecies concept in various taxa of animals is subject of debates since its very existence. In case of the species of the lygaeoid subfamily Geocorinae there are multiple examples of species consisting of up to nine subspecies which were mostly described as varieties or forms before the middle of 20th century, but upgraded to valid subspecies subsequently, usually without providing any arguments. As part of an integrated taxonomic study on the Palaearctic representatives of Geocorinae, the status of the subspecies of Geocoris (Piocoris) erythrocephalus (Lepeletier & Serville, 1825) was revisited. A critical review of the literature available and our studies, involving analysis of COI sequences, morphological examination and distribution data processing with the use of Geographic Information System, concluded that two of the three subspecies, G. e. erythrocephalus and G. e. marginellus Horváth, 1907, can be considered valid, while G. e. litoreus Horváth, 1895, is merely a phenotypically manifested infrasubspecific genetic variety of G. e. erythrocephalus, with no taxonomic value as it was suggested by earlier study of another author. Besides the interpretation of evidence, the applicability of the subspecies concept in Geocorinae is discussed as well.